The measurement of the reproduction number - Georg Quaas (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2021)
The German Robert Koch Institute aims to "protect the population from disease and improve their state of health" (RKI 2017). To this end, it develops concrete, research-based recommendations for policymakers and makes data available to the expert public. Since March 4, 2020, it has been publishing the numbers of coronavirus infections reported by health authorities daily; since March 9, these data have included the numbers of people who have died of or with COVID-19; and since March 25, the RKI has reported the estimated numbers of those who have recovered. The important reproduction number, reported daily since April 7, largely replaced all other criteria used for decision-making, but this was the case only for a few months. Since the second wave of the pandemic, the mere number of new infections and later the incidence number proved to be more plausible and practicable in Germany. This paper aims to show that RKI's reproduction number is neither theory-based nor particularly reliable. Nevertheless, there is a simple way to determine the reproduction number precisely and in accordance with epidemiologic theory. The correct calculated Rnumber could serve as reliable compass leading health policymakers through the months of an epidemic.
Keywords: C32; C61; I12; I18; J11; 330; Classic epidemic model; reproduction number; contact rate; COVID-19; mathematics ofhighly infectious diseases; public health policy